PENGARUH FINANCIAL DISTRESS DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Maya, Arista Lestari; Haryetti, Haryetti; Ahmad, Fathoni Fauzan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to analyze the Effect of Financial Distress and Financial Performance on Company Value Mediated by Profit Management in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2018. The population used in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018 with a total of 159 companies. The sample selection used a nonprobability sampling approach with a purposive sampling method. The sample of this research were 66 companies that fulfill certain criteria. After the outlier test, the companies analyzed to 34 companies in the 5 years of observation obtained 170 data. The results of this study found that 1) Financial distress had no effect on firm value. 2) Financial performance affects the value of the company. 3) Earnings management had no effect on the value of the company. 4) Financial distress had no effect on firm value through earnings management. 5) Financial performance affects the value of the company through earnings management.Keywords : financial distress, financial performance, company value, earnings management